Study on Performance of Quarry Dust as Partial Replacement of Fine Aggregate in Concrete - Nallamothu, Sravya; Sai Kalyan, P. Mittu; Vinay, G.; Sameer Baba, S. K.; Sai Charan, S. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The concept of replacement of natural fine aggregate by quarry dust which is highlighted in the study could boost the consumption of quarry dust generated from quarries. By replacement of quarry dust, the requirement of land fill area can be reduced and can also solve the problem of natural sand scarcity. The availability of sand at low cost as a fine aggregate in concrete is not suitable and that is the reason to search for an alternative material. Quarry dust satisfies the reason behind the alternative material as a substitute for sand at very low cost. It even causes burden to dump the crusher dust at one place which causes environmental pollution. Aggregates normally accounts 70% to 80% of the entire volume of concrete, while water and cement account 20% to 30%. These percentages affect the mechanical properties of concrete. So, replacing of any material by industrial waste can create a positive impact on environment and reduces the intensive use of energy and natural resources (aggregate mining). There are plenty of industrial wastes that can be used in concrete as either replacement of fine aggregate. This project has focused on evaluating the opportunity of using of waste materials which is the quarry dust as a replacement of fine aggregate.M40 grade concrete was prepared with 0%, 10%, 20%, 30%, 40% partial replacement of sand with quarry dust. Mechanical and fresh properties of concrete were carried out at 3, 7 and 28 days respectively.
Keywords: Quarry Dust; Concrete; Quarry Dust Concrete; Crusher Dust Concrete